How Job Insecurity Affects Organizational Commitments Through Job Satisfaction - Devyani, Shindy; Meria, Lista (APTISI Transactions on Management (ATM), 2023)
Work productivity can be optimal if the human resources have high organizational commitment. This study aims to determine the effect of job insecurity on organizational commitment with job satisfaction as a mediation carried out by employees of PT. Pelangi Elasindo. This study uses a type of causal research. The sampling technique used simple random sampling with a sample size of 208 employees and data analysis using SEM-PLS. The results of the study show that there is an influence between job insecurity on job satisfaction and Job Insecurity on organizational commitment. While job satisfaction has no effect on organizational commitment, there is no evidence of a mediating effect between job insecurity and organizational commitment. From the results obtained, it can be seen that job insecurity plays an important role in job satisfaction and organizational commitment. This study has implications for management to reduce job insecurity and strengthen employee commitment.